Effect of multiaxiality, stacking sequence and number of off-axis layers on the mechanical response and damage sequence of carbon/epoxy composite laminates under static loading. (12th April 2020) - Kalteremidou, Kalliopi-Artemi; Hajikazemi, Mohammad; Van Paepegem, Wim; Van Hemelrijck, Danny; Pyl, Lincy
Abstract: The mechanical response and damage sequence of composite materials are nowadays still a topic of ongoing research. However, many parameters influencing their overall behavior are still not thoroughly taken into consideration. The effect of multiaxial stresses, the distinction between balanced and unbalanced configurations and the influence of the number of off-axis layers are just a few to mention. Experimental data regarding the effect of all these parameters on the damage progression in composites is of great importance, since it is proven that commonly used failure criteria, neglecting the occurring damage mechanisms, cannot always predict the material response. In this work, a study of the influence of all these parameters is attempted, by testing carbon/epoxy laminates with different off-axis angles to account for different multiaxiality. Both balanced and unbalanced laminates are taken into account, considering the lack of experimental evidence in literature regarding the latter case, and significant differences between the two lay-ups are reported for the first time. Finally, the influence of the number of the off-axis layers on the mechanical response in conjunction with the previous parameters is also studied through elaborate damage observations.